FDR [videorecording (DVD)] - McCullough, David G.; Grubin, David (PBS Home Video ; Distributed by Paramount Home Entertainment, 2008)
Learn the story of one of America's most beloved Presidents. Includes rare archival footage and home movies as well as fascinating interviews with family members, friends, biographers, and eyewitnesses to the Roosevelt saga.